Possibilities of combating activities on the inland water of the Republic of Poland on the example of the River Fleet of the Navy in Pińsk - Bieniecki, Ireneusz (Armia kontra natura, 2020)
The article presents the restrictions related to the conduct of combat operations by the vessels of the Navy River Fleet in Pinsk. It provides discussion of issues such as war doctrine of the Second Polish Republic and river fleets, geographical characteristics of Polesie, possibilities of conducting activities by the Pinsk Fleet in the assessment of commanders and superiors, as well as technical parameters of vessels and the resulting restrictions.